2013
DOI: 10.1194/jlr.m039545
|View full text |Cite
|
Sign up to set email alerts
|

New horizons for lipoprotein receptors: communication by β-propellers

Abstract: sorLA/LR11], the LARGE receptors [low-density lipoprotein receptor-like protein 4, 5, and 6 (LRP4, LRP5, and LRP6)] and the GIANT receptors {low-density lipoprotein receptor-like protein 1, protein 1B, and protein 2 [LRP1, LRP1B, and LRP2 (also known as megalin)]} ( Fig. 1A ). Unrelated to size, the LRs are all modularly constructed from a limited subset of three different domains: the complement type repeat (CR)-domains, the epidermal growth factor (EGF)-like domains, and the ␤ -propellers containing YWTDrepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 83 publications
0
11
0
1
Order By: Relevance
“…The C-terminal domain (residue 334-596) has a canonical α/β hydrolase fold with a central eightstranded, mixed β-sheet flanked by α-helices on both sides. A short α-helix (helix α1, residues [5][6][7][8][9][10][11][12][13][14] in the N-terminal region protrudes from the β-propeller domain and connects it to the hydrolase domain.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The C-terminal domain (residue 334-596) has a canonical α/β hydrolase fold with a central eightstranded, mixed β-sheet flanked by α-helices on both sides. A short α-helix (helix α1, residues [5][6][7][8][9][10][11][12][13][14] in the N-terminal region protrudes from the β-propeller domain and connects it to the hydrolase domain.…”
Section: Resultsmentioning
confidence: 99%
“…This fold is associated with a variety of different biological functions, such as regulation of multi-domain proteins [2], structural stabilization, metal-ion binding [3,4], ligand binding [5] and catalysis [6]. Moreover, several proteins containing β-propeller motifs have been reported to be associated with human diseases, such as cancer, neurodegeneration and arthritis [7].…”
Section: Introductionmentioning
confidence: 98%
“…Different families of endocytosis receptors have been identified but our understanding of how their ligands are released at low pH after endocytosis remains incomplete. For the low-density lipoprotein (LDL) endocytosis receptor it has been shown that an intramolecular conformational rearrangement of domains discharges ligands 1 but whether such a conformational change mechanism applies to other endocytosis receptors is not clear 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The amino-terminal LBD domain confers ligand specificity, consisting of cysteine-rich complement-type ligand binding-type repeats (LBRs, sometimes called type A repeats). The EGF-precursor domains participate in the pH-dependent release of bound ligands after endocytosis and contain a mixture of EGF receptor-like repeats (EGF-repeats) and YWTD (Tyr-Trp-Thr-Asp) β-propeller repeats (Beglova and Blacklow, 2005 ; Andersen et al, 2013 ; reviewed in Li et al, 2001 ). The intracellular domain is less conserved between the family members, but each of the core members contain at least one NPxY (Asn-Pro-X-Tyr) motif that functions in protein interaction/signal transduction (Trommsdorff et al, 1998 ; Howell et al, 1999 ; Gotthardt et al, 2000 ) and endocytosis (Chen et al, 1990 ).…”
Section: Lipoprotein Receptorsmentioning
confidence: 99%